Structured ICT learning as local content curriculum: The practice at SD Budiluhur - Almira Rahma Fadhila (Hipkin Journal of Educational Research, 2025)
The integration of Information and Communication Technology (ICT) into learning at the primary school level is a key effort in addressing the challenges of 21st-century education. This study is driven by the need to understand how ICT is concretely integrated in primary schools, particularly in curriculum planning and the implementation of learning that aligns with students' needs. Employing a qualitative research design with a case study method, this research aims to provide an in-depth and contextual description. Data collection techniques include interviews and observations. The objective of this study is to describe the ICT integration process at Budiluhur Primary School and to identify the supporting and inhibiting factors that influence its success. The findings reveal that Budiluhur Primary School has developed a structured model of ICT integration through internal policies, continuous teacher training, infrastructure development, and the establishment of a school ICT development team. The study also highlights that despite challenges such as technical limitations and varying levels of teacher competence, successful integration can still be achieved through collaborative strategies, visionary leadership, and strong internal support from the school.   Abstrak Penerapan Teknologi Informasi dan Komunikasi (TIK) dalam pembelajaran pada jenjang sekolah dasar menjadi salah satu upaya penting dalam menghadapi tantangan pendidikan abad ke-21. Penelitian ini dilatarbelakangi oleh kebutuhan untuk memahami integrasi TIK yang dilakukan secara nyata di sekolah dasar, khususnya dalam perencanaan kurikulum dan pelaksanaan pembelajaran yang relevan dengan kebutuhan peserta didik. Penelitian ini menggunakan desain penelitian kualitatif dengan metode studi kasus untuk memberikan gambaran yang mendalam dan kontekstual. Teknik pengumpulan data dilakukan melalui wawancara dan observasi. Tujuan penelitian ini adalah untuk mendeskripsikan proses integrasi TIK di SD Budiluhur serta mengidentifikasi faktor-faktor pendukung dan penghambat yang memengaruhi keberhasilannya. Hasil penelitian menunjukkan bahwa SD Budiluhur telah mengembangkan model integrasi TIK yang terstruktur melalui kebijakan internal, pelatihan guru secara berkelanjutan, pengembangan infrastruktur, dan pembentukan tim pengembang TIK sekolah. Temuan ini juga mengungkapkan bahwa meskipun terdapat kendala seperti keterbatasan teknis dan perbedaan tingkat kompetensi guru, keberhasilan integrasi tetap dapat dicapai melalui strategi kolaboratif, kepemimpinan yang visioner, dan dukungan internal yang kuat dari pihak sekolah. Kata Kunci: implementasi kurikulum TIK; integrasi teknologi; pembelajaran TIK; sekolah dasar